The Effect of Osmopriming on Seed Germination and Early Seedling Characteristics of Carum carvi L. - Iman Mirmazloum; Attila Kiss; Éva Erdélyi; Márta Ladányi; Éva Zámboriné Németh; Péter Radácsi (Agriculture, 2020)
Two experiments (in Petri dishes and in soil) were conducted to investigate the effects of osmopriming on seed germination and the early seedling characteristics of caraway (Carum carvi L. var. annua). The priming treatments in the Petri dish experiment were: polyethylene glycol (5%, 10% and 20%), KNO3 (0.5%, 1% and 2%) and KCL (1%, 2% and 4%) with three different soaking times (12, 24 and 36 h) along with control (non-primed seeds). Only polyethylene glycol and H2O were applied in the cell tray experiment, which were then compared with the non-primed seeds. In the Petri dish experiment, all three priming reagents significantly enhanced seedling length, with the most effective treatments being 5% PEG, 2% KNO3 and 1% KCL for 12 h. The plumule dry weights were also increased significantly after PEG (20% for 36 h), KNO3 (2% for 24 and 36 h) and KCL (1% for 12 h) treatments in comparison with the control. In the soil experiment, osmopriming with PEG significantly improved the germination rate (GR) and percentage, the plumule dry and fresh weights and the plumule length of caraway seedlings when compared with the control. A 23% higher germination percentage was recorded for the seeds treated with 5% PEG for 24 h as compared with the non-primed seeds. The PEG-primed seeds produced significantly longer seedlings when treated with 5% PEG for 24 h. All of the applied PEG treatments significantly enhanced the plumule fresh and dry weights, with the best outcomes being after 5% PEG (24 h) and 10% PEG (36 h) treatments, respectively. The 12-h hydro-priming also significantly enhanced all of the studied germination parameters when compared to the control. The results of the presented experiments show the significant positive effects of seed priming on caraway germination and how early seedling performance can easily be adopted by producers.